Detection of Low Dose-Gamma Irradiated Spices by Photostimulated Luminescence (PSL) Technique - Shamsudin, Farha Mizana; Yasir, Muhamad Samudi (Journal of Science and Technology, 2022)
Photostimulated luminescence (PSL) has been widely used as a rapid screening technique for the detection of various irradiated foods. This study aims to investigate the efficacy of the PSL technique in the detection of low dose-gamma irradiated spices available in the Malaysia market. Samples of clove, coriander, fenugreek, turmeric powder and curry powder were irradiated at very low doses; 0 (control), 0.2, 0.5 and 1 kGy using Cobalt-60 as a source. PSL measurements and analysis were undertaken under subdued lighting following EN 13751 methods. The PSL value in the form of photon counts (PCs/60s) of all samples as a function of the irradiation dose after 7 days of storage were determined which revealed that the PSL value increases proportionally to the radiation dose applied. The PSL also was able to discriminate between the non-irradiated (<700 PCs/60s, negative) and irradiated (>5000 PCs/60s, positive) samples after 7 days of storage. Coriander generates the highest PCs at the lowest dose (0.2 kGy) and highest dose (1 kGy) after that storage period. The PSL value of all spice samples is considered accurate and consistent at all irradiation doses. This technique is highly reliable for the detection of irradiated spices available in the Malaysia market.